2018
DOI: 10.5765/jkacap.180013
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on the Process of the Mental Health Assessment and Intervention after the Sewol Ferry Disaster: Focusing on Survivors among Danwon High School Students

Abstract: This study aimed to identify the process of psychosocial assessment, the experience of intervention, and the improvement after the disaster that Danwon high school students survived from the sinking of the Motor Vessel (MV) Sewol in South Korea on April 16, 2014. Methods: We conducted in-depth qualitative research using individual interviews from January to February 2017. Twenty-one of 75 Danwon high school students survived by the MV Sewol disaster were studied. Two interviewers participated in the in-depth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The search mission for victims of the disaster ended on November 11, 2014; the bodies of nine victims were never recovered. Recent follow-up studies have reported that survivors of the Sewol ferry disaster have suffered from PTSD symptoms as well as depression, insomnia, anxiety, and aggression even several years after the disaster ( Lee et al, 2018 ; Lee et al, 2018 ). Embitterment among the bereaved families has increased along with PTSD, anxiety, and complicated grief over time ( Yun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The search mission for victims of the disaster ended on November 11, 2014; the bodies of nine victims were never recovered. Recent follow-up studies have reported that survivors of the Sewol ferry disaster have suffered from PTSD symptoms as well as depression, insomnia, anxiety, and aggression even several years after the disaster ( Lee et al, 2018 ; Lee et al, 2018 ). Embitterment among the bereaved families has increased along with PTSD, anxiety, and complicated grief over time ( Yun et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines were established in a semi-structured open-ended questionnaire format, based on previous literature. 13 14 Interviews began with the question, “please freely share your experiences and changes from the present perspective, five years after the Sewol Ferry accident,” with other questions being added as the participant’s narrative proceeded. Interviewees discussed the overall changes following the disaster, psychological and physical changes, major difficulties, and help needed.…”
Section: Methodsmentioning
confidence: 99%
“…The members of the Korean Academy of Child and Adolescent Psychiatry have gained much experience in the field of disaster psychiatry through several serious incidents, including a single incident of death witnessed by fourth graders at an elementary school in 2007 [39], suicidal death among elementary school students from 2011 to 2015 [40], and the Sewol Ferry disaster of 2014 [41]. The academy organized a new committee for disaster and trauma, and the committee created guidelines on the COVID-19 outbreak, including "Coping with the stress of COVID-19 epidemic: tips for families getting through school closing period" [42] and "Tips for adolescents: Coping with the stress of COVID-19 epidemic" [43].…”
Section: School Closure-associated Mental Health Issues Among Childrenmentioning
confidence: 99%